Sprint step-type specific characteristics of anthropometric and kinematic variables in sprinting acceleration - Naito, H.; Kariyama, Y.; Yamamoto, K.; Tanigawa, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the anthropometric and the kinematic characteristics during the acceleration phase between stride frequency (SF)-type and stride length (SL)-type sprinters. Seventeen sprinters participated in this study. The maximal 60-m sprints and anthropometric measures were obtained from subjects. Two sprints were recorded by using high-speed cameras. Sprint velocity, SL, SF and their underlying kinematic variables were calculated. Cluster analysis was used to classify the subjects into the SF or SL -type groups (step-type) as indicated by the ratio of the SF and SL at maximum velocity. The SF-type group showed shorter lower limbs length, flight time, lower the height of center of mass at takeoff, smaller swing motion and faster forward rotation of the shank and foot segments than the SL-type group. This study showed the noticeable differences between SFtype and SL-type sprinters were not only in swing motion but also in push-off motion.